Dynamic Topochemical Reaction Tuned by Guest Molecules in the Nanospace of a Metal–Organic Framework - Kusaka, Shinpei; Kiyose, Atsushi; Sato, Hiroshi; Hijikata, Yuh; Hori, Akihiro; Ma, Yunsheng; Matsuda, Ryotaro (Journal of the American Chemical Society, 2019)
Reaction in well-designed solids allows yielding products with high selectivity and unique compounds that cannot be obtained in solution. However, the precise tuning of the arrangement of reactants in solids for the versatile application of solid-phase reactions remains a challenging subject. Here, a [2 + 2] photocyclization reaction at different positions of the carbon–carbon bonds is described in which the spatial arrangement of 4-styrylpyridines (4-spy) is changed by guest molecules in a flexible metal–organic framework. The 4-spy molecules undergo photodimerization between two carbon–carbon double bonds in the guest-free framework, whereas a reaction between olefinic and aromatic carbon–carbon bonds or the absence of reaction takes place in the solvent-incorporated form. This reactivity, which can be termed as “dynamic topochemistry” contributes to enforce the applicability of solid-phase reactions in synthetic chemistry.